Power, rights and play: control of play in school grounds, an action research project from Wales. Issue 6 (18th August 2019) - Tyrie, J.; Sarwar, S.; Dumitrscu, S.; Mannello, M.; Haughton, C.; Ellis, C.; Connolly, M.
ABSTRACT: This paper focuses on the role of control, power and people in utilising school grounds for play. Despite children's right to play in statute and evidence that play has positive outcomes for children, evidence suggests that school grounds are under-utilised. An action research methodology was adopted with three primary schools in Wales (UK), opening school grounds after school hours. Findings indicate that power and control are factors affecting accessibility and use of outdoor spaces, particularly in relation to who was allowed access to play spaces, where children were allowed, as well as when and what types of play were acceptable.